Vaccine impacts E. coli O157 in feedlot cattle - Fox, J.T.; Thornton, A.B.; Jacob, M.E.; Thomson, Daniel U.; Drouillard, James S.; Nagaraja, Tiruvoor G. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Many human foodborne illnesses are caused by pathogens commonly harbored by food animals. Escherichia coli O157 is one of these pathogens commonly isolated from beef cattle feces and can enter the food chain at harvest. In addition to the human health concerns, this pathogen has important economic implications. Costly recalls of beef products and loss of consumer confidence associated with outbreaks of foodborne illness can affect profitability on many levels of production. In the past 10 years, E. coli O157 has cost the beef industry an estimated $2.67 billion. A portion of this expense is allocated to government and industry research. Methods to intervene and reduce the opportunity of these pathogens to enter the food chain have been tested and implemented both pre- and postharvest. The focus of this experiment was to evaluate the effectiveness of a novel vaccine technology to reduce E. coli O157 shedding in feeder cattle prior to harvest. A relatively new vaccine technology developed by Epitopix (Wilmar, MN) targets pathogenic bacteria based on their inherent requirement for iron. Vaccines developed with this technology target siderophore receptor and porin proteins (SRP) of specific bacteria and disrupt their iron transport systems, which ultimately causes death of the organisms. Preliminary experiments have shown that SRP vaccines reduce fecal shedding of Salmonella Newport and E. coli O157 in experimentally infected mice. In two experiments involving experimentally infected cattle, an SRP vaccine for E. coli O157 reduced fecal shedding of the experimental strain of E. coli O157. Given the success of this vaccine in cattle challenged with E. coli O157, the objective of the current experiment was to test the efficacy of the E.coli O157 SRP vaccine in feedlot cattle naturally infected with E. coli O157.
Keywords: Beef; Cattle; E. coli O157